Representasi Problematik Anak Akibat Broken Home Dalam Film Susah Sinyal - Emie Oktavianie; Abbyzar Aggasi (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2023)
Family has an important role in human life as the first place to learn. However, the Broken Home family has a negative impact on children, such as negative self-concept and difficulties in socializing. The film "Susah Signal" attracts the attention of the writer because it depicts the problems of Broken Home children and the disharmonious relationship between a child and his mother due to the mother's busy pursuit of a career. This study uses a qualitative descriptive research method with a content analysis approach, which involves both explicit and implied communication content. Primary data was collected through documentation in the form of signs obtained from the film "Susah Signal". The data collection method used was content analysis, in which the researcher conducted a descriptive analysis of the dialogues and shows shown in the film. In content analysis, the researcher explains each scene and dialogue that has been collected. In the film "Susah Signal", the lack of communication between mother and child makes Ellen have a control nature in applying rules that must be followed without exception. Poor communication leads to misunderstandings and sources of conflict. The impact of Broken Home children's problems seen in the film "Susah Signal" can be concluded that the analysis shows that children's problems in a Broken Home situation have a significant influence on family relationships and children's behavior.